Women Empowerment in Sustainable Tourism Development in Tenganan Pegringsingan Tourism Village, Karangasem, Bali - Dewi, Kadek Rahayu Teresna; Widana, Ida Bgs Gede Agung; Aridayanti, Dewa Ayu Nyoman (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This research was conducted with the aim of identifying the dimensions of empowerment, especially in the Tenganan Pegringsingan Tourism Village and to see the relationship between the dimensions of women's empowerment and the elements of sustainable tourism destination development according to Tourism and Creative Economy Ministerial Regulation Number 9 of 2021 concerning guidelines for developing sustainable tourism destinations. The exploratory factor analysis method was used to analyze the data that had been collected using a purposive sampling technique with a total of 140 samples. The results of the research show that 7 (seven) new dimensions have been formed that can describe women's empowerment in Tenganan Pegringsingan Village. The seven dimensions formed have fulfilled the elements that can support the realization of a sustainable tourism destination in the Tenganan Pegringsingan Tourism Village in accordance with the guidelines for developing sustainable tourism destinations.